Comparative in vitro study of the marginal apical sealing capacity of Sealapex® and Endofill® Sealers - Renato Interliche; Mauro Celso Boer; Priscilla Viviana Mamprin Casaroto; Douglas Giordani Negreiros Cortez (RGO: Revista Gaúcha de Odontologia)
Objective: To evaluate the apical seal obtained with two sealers: Sealapex (Kerr-Sybron, Orange, USA) a calcium hydroxide-based sealer and Endofill (Dentsply, Petrópolis, Brazil) a zinc oxide eugenol-based sealer. Method: Twenty four extracted single-rooted human teeth were divided into two groups, with ten each, instrumented and filled by lateral condensation technique with gutta-percha and one of the sealers. Four teeth were used as positive and negative control. After filling, all specimens were coated with nail vernish except around the apical foramen (the negative control group was completely covered), and then immersed in indian ink for 96 hours, decalcified, dehydrated and diaphanized. Results: The extent of staining was examined under a stereo microscope and the data were statistically analyzed by the Tukey test. Numerically Sealapex (Kerr-Sybron, Orange, USA) experimental group had lower levels of marginal leakage than Endofill (Dentsply, Petrópolis, Brasil). The negative control exhibited no leakage and in the positive control leakage was complete. There was no statistically significant differencebetween the sealers. Conclusion: The sealers showed similar apical sealing ability. Neither of the sealers in this study completely prevented leakage.